Bridging Policy and Practice: Challenges in Implementing Inclusive Admission Policy (PPDB) In Indonesian Schools - Sriwidayani Syam; Gita Irawanda; By Tri Agung Kr.j Tompong (Indonesian Journal of Educational Studies, 2025)
Abstract. This study explores the challenges in implementing the inclusive school admission policy (PPDB) in Indonesia through a comprehensive literature review. Focusing on three core areas, policy frameworks, infrastructure readiness, and teacher preparedness, the study identifies systemic barriers to achieving effective inclusion in Indonesian schools. Thematic analysis of national regulations, academic literature, and policy evaluations reveals persistent gaps between policy and practice, particularly at the regional and school levels. Inadequate infrastructure and limited accessibility, especially in rural areas, remain critical obstacles. Moreover, many educators report insufficient training, lack of confidence, and minimal institutional support in working with students with special needs. These interrelated challenges indicate that inclusive education in Indonesia requires more than policy declarations; it demands systemic reform. The study recommends strengthening vertical policy alignment, increasing funding for inclusive facilities, integrating inclusive pedagogy into teacher education, and improving cross-sector collaboration and data systems. Findings contribute to the global discourse on inclusive education by highlighting the need for a context-sensitive and multi-level approach to equity and access. Keywords: inclusive education, PPDB, Indonesia, teacher readiness, school infrastructure, education policy